Konsep dasar ekonomi berkelanjutan: memahami integritas ekonomi, sosial, dan lingkungan - putra, ryan (Maliki Interdisciplinary Journal, 2025)
Sustainable economy is a concept that integrates three main pillars: economy, social, and environment. In the current global context, understanding this integration is crucial to achieving sustainable development. This article discusses how sustainable economy focuses not only on economic growth but also on social welfare and environmental protection. With this approach, it is hoped that a balance can be created between human needs and the sustainability of natural resources. This research employs a qualitative analysis method to explore sustainable economic practices across various sectors. The results indicate that effective integration among the three pillars can optimize social and economic benefits while preserving environmental integrity. Moreover, government policies and community participation play a significant role in supporting sustainable economy. This article aims to provide deeper insights into the importance of integrating economic, social, and environmental aspects in achieving sustainable development goals.